Rescue of stranded persons. C18. Rescue of stranded passengers in the Arctic - Meidell, Annette; Olsen, Steve (Universitetet i Stavanger, 2018)
Chapter in report. Whole report available at http://hdl.handle.net/11250/2578301 Since we (the authors) could not be a part of the whole SARex 3 exercise this year, we joined the expedition later than the rest of the participants. We gladly accepted the invitation from the Governor of Svalbard, Kjerstin Askholt, and her staff in Longyearbyen to join their service vessel, MS Polarsyssel, to meet The Norwegian Coast Guard’s vessel, (NOCGV) Svalbard, at the location where the last part of the SARex expedition would take place. MS Polarsyssel and the Governor of Svalbard’s staff would this year participate in this last part of the SARex 3 exercise with the aim to prepare and handle the situation of a large number of stranded passengers in the Arctic. In this part of SARex 3 exercise, the rescue group from Longyearbyen Red Cross would also participate and practice in this search and rescue (SAR) exercise; see [1]. The governor of Svalbard is both the chief of police and accorded the same authority as a county governor on the mainland. Rescue service is one of the governor’s tasks, and the governor normally leads all rescue missions in Svalbard. The Joint Rescue Coordination Center (JRCC) North in Bodø has the overall operational responsibility during search and rescue operations north of 65 degrees north. The operations are coordinated either directly from JRCC North or through the Governor of Svalbard. For more information concerning this, see [2]. This report will focus on the search and rescue (SAR) exercise from the point of view of the “late arrivers” (as we were called throughout the rest of the SARex 3 expedition)